POTENSI SUMBERDAYA MINERAL DISTRIK WINDESI KABUPETAN TELUK WONDAMA - Hermina Haluk (INTAN Jurnal Penelitian Tambang, 2019)
Geologically the Windesi area is composed of sedimentary rocks from the Kembelangan Group, which are in the Middle Jura to the Middle Miocene. The Kembelangan group suppressed in harmony with Imskin limestone (KTi) which is in the Upper Cretaceous to the Middle Miocene. Thus, it has quite a variety of mineral potential. Potential Mineral Resources in the Windesi District are classified as Non-Metallic Minerals consisting of limestone, sandstone, shale and assorted gravels. Possible occurrence of limestone in Windesi District found in Wamesa Tengah village, Windesi village, Sombokaro village, Yopmios village and Sandey village with an estimated reserve area of 3,093,325 Ha. Sandstones found in Sandey village and partly in Wamesa Tengah village, as well as in Windesi village. The possible occurence of sandstone in the Windesi District area is quite large with an estimated reserve area of 156,290.51 Ha. Shale scattered in the middle of Sandey village and in the northern part of Windesi village and partly in Yopmios village with a reserve area of approximately 414,845.19 Ha. Assorted gravels potential found in Sandey village in the west and along the coast of Tanjung Ronsore in the north to northeast with a reserve area of approximately 2,973.17 Ha.